2023
DOI: 10.1097/pcc.0000000000003196
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Delirium in Children: A Systematic Review and Meta-Analysis*

Abstract: OBJECTIVES: Pediatric delirium (PD) is a neuropsychiatric syndrome caused by a complex interplay between predisposing factors (e.g., age, cognitive impairment), acute illness, and environmental triggers. PD is associated with substantial morbidity and mortality. The objective of this study is to systematically review and evaluate factors associated with PD in hospitalized pediatric patients. DATA SOURCES:A systematic search of PubMed, Embase, Ovid Medline, Webof-Science, Cochrane, CIHNAL, and Google Scholar da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
26
1
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 53 publications
(199 reference statements)
2
26
1
3
Order By: Relevance
“…Ista E, Traube C, de Neef M, et al; Dutch Multidisciplinary Pediatric Delirium Guideline Group: Factors Associated With Delirium in Children: A Systematic Review and Meta-Analysis (8).…”
Section: What About Factors Associated With Delirium During Critical ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Ista E, Traube C, de Neef M, et al; Dutch Multidisciplinary Pediatric Delirium Guideline Group: Factors Associated With Delirium in Children: A Systematic Review and Meta-Analysis (8).…”
Section: What About Factors Associated With Delirium During Critical ...mentioning
confidence: 99%
“…The authors describe information from 24 studies in which 54 factors were found associated with delirium. In the meta-analysis these findings are reduced to seven factors associated with greater odds of developing delirium during pediatric critical illness (8). In the accompanying editorial our writers propose that it is time to include delirium screening as part of our “vital sign” monitoring (9).…”
Section: What About Factors Associated With Delirium During Critical ...mentioning
confidence: 99%
“…Ista et al (12), a team comprised of well-established and prominent leaders in the field of pediatric delirium, present the findings of an important meta-analysis on delirium in the PICU, reporting risk factors for developing delirium during pediatric critical illness. By including 24 studies and more than 10,000 pediatric patients in their review, the authors identified seven risk factors associated with greater odds of developing delirium.…”
mentioning
confidence: 99%
“…Of these, only one, the presence of developmental delay, was nonmodifiable. The remaining six risk factors were modifiable and these included (in descending order according to the magnitude of the strength of their association with the odds of developing delirium): need for mechanical ventilation, use of physical restraints, use of benzodiazepines, vasoactive medications, opiates, or steroids (12).…”
mentioning
confidence: 99%
See 1 more Smart Citation